ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI KOPI ROBUSTA DI KECAMATAN KELING KABUPATEN JEPARA - Putri, Meira Pradipta; Setiadi, Agus; Budiraharjo, Kustopo (Universitas Wahid Hasyim, 2023)
The study aimed to analyze robusta coffee production and analyze the factors that influence to robusta coffee production in Keling District. The research locations are Tempur Village and Damarwulan Village, Keling District, Jepara Regency. The research method used is a survey method with purposive random sampling, with 100 respondents of robusta coffee farmers. The data analysis method used is descriptive analysis with the production function Cobb-douglas. Research shows that robusta coffee farmers in Keling District have the following characteristics: the majority are male, the average age range is 20-49 years, the majority have primary school education, the majority have been farming for more than 20 years, the number of dependents on the majority of farmer families is 4-6 people, the majority of respondents make farming as their main job. The average production of robusta coffee in Keling District is 747,24 kg/ha/year. The production factors of capital, land area, labor, fertilizers, pesticides simultaneously have a positive and significant effect on robusta coffee production in Keling District with a coefficient of determination of 0,942. Partially, the variables of capital, labor, fertilizers, and pesticides have a significant effect on robusta coffee production. The variable that has the most significant effect on robusta coffee production is capital (X1) with a regression coefficient of 0,475 in units of IDR/year.